An Analysis of The Main Character’s Conflict in “The Fault in Our Stars” Novel by John Green. - Halimah Tussadiah (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2023)
This study aimed at analysing the conflict and the process of how the conflict contained in the novel by John Green entitled The Fault in Our Stars. In this study descriptive qualitative research was applied. In order to discover the answer, the writer tried to find out the main character’s internal conflicts described in the novel of The Fault in Our Stars written by John Green, the main character’s external conflict described in the novel of The Fault in Our Stars, and the dominant type of the main character in The Fault in Our Stars novel. The results were man vs self 53 (36.30%), man vs man 49 (33.56%), man vs nature 27 (18.49%), man vs society 17 (11.64%), and the dominant one was man vs self 53 (36.30%).